BAHASA INDONESIA SEBAGAI ALAT KOMUNIKASI MODERN - ROSTINA, ROSTINA (JURNAL ILMIAH SIMANTEK, 2023)
The use of good and correct Indonesian will produce good and correct thoughts as well. The fact that Indonesian is used as a form of identity in the means of communication in modern society. Language Indonesian is flexible and able to carry out its function as a means of communication in modern society. So Indonesian is one of the important aspects of social life. Indonesian is the language that unites the diverse ethnic Indonesian nation, which unites the Indonesian people, who are diverse in ethnicity and culture. The open nature of the Indonesian language allows become a modern language in accordance with the growth and development of advanced science and technology. Indonesian language needs to continue its development, especially the development of vocabulary. The development of Indonesian vocabulary must be balanced with the development of science so that the quality of its expression meets the demands of its position and function in the life of Indonesian society and its function in the present and future life of Indonesian society.